Italian health professionals on the mandatory COVID-19 vaccine: An online cross-sectional survey - Luca Ghirotto; Matías Eduardo Díaz Crescitelli; Ludovica De Panfilis; Luana Caselli; Arianna Serafini; Luca De Fiore; Gian Maria Galeazzi; Gian Maria Galeazzi; Massimo Costantini (Frontiers Media S.A., 2022)
Italy was the first country in Europe to make vaccination against COVID-19 mandatory for healthcare professionals by imposing restrictions in cases of non-compliance. This study investigates the opinions of the Italian healthcare professionals' categories affected by the regulation. We performed a qualitative online survey: the questionnaire comprised both close- and open-ended questions. The final dataset included n = 4,677 valid responses. Responses to closed-ended questions were analyzed with descriptive statistics. The framework method was applied for analyzing the open-ended questions. The sample spanned all health professions subject to compulsory vaccination, with a prevalence of physicians (43.8%) and nurses (26.3%). The vaccine adhesion before the introduction of the obligation was substantial. 10.4% declared not to have adhered to the vaccination proposal. Thirty-five percent of HPs who opted not to get vaccinated said they experienced consequences related to their choice. The trust in the vaccine seems slightly cracked, demonstrating overall vaccine confidence among professionals. Nonetheless, our results show that whether (or not) professionals adhere to vaccination is not a reliable indicator of consent to how it was achieved. There are criticisms about the lawfulness of the obligation. The data show a great variety of participants interpreting their roles concerning public and individual ethics. The scientific evidence motivates ethics-related decisions-the epidemic of confusing and incorrect information affected professionals. The Law triggered an increased disaffection with the health system and conflicts between professionals. Dealing with the working climate should be a commitment to assume soon.